2013
DOI: 10.1681/asn.2013010076
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Mediates Renal Proximal Tubule Recovery from AKI

Abstract: AKI induces the renoprotective upregulation of survivin expression in kidney epithelial cells, but the underlying mechanisms have not been identified. To determine the role of survivin in renal recovery from AKI, we generated mice with renal proximal tubule-specific deletion of survivin (survivin ptKO ). Renal survivin expression increased substantially in response to ischemia-reperfusion (I/R) injury in control littermates but remained minimal in survivin ptKO mice. Functional and histologic data indicated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 40 publications
2
84
0
Order By: Relevance
“…51,52 Tubular injury was defined as tubular dilation, tubular atrophy, tubular cast formation, vacuolization, degeneration, and sloughing off of tubular epithelial cells or loss of the brush border and thickening of the tubular basement membrane. The tubules were evaluated according to the following scoring system: 0= no tubular injury; 1#10% tubules injured; 2=11%-25% tubules injured; 3=26%-50% tubules injured; 4=51%-74% tubules injured; and 5$75% tubules injured.…”
Section: Quantitative Assessment Of Labeling Efficiencymentioning
confidence: 99%
“…51,52 Tubular injury was defined as tubular dilation, tubular atrophy, tubular cast formation, vacuolization, degeneration, and sloughing off of tubular epithelial cells or loss of the brush border and thickening of the tubular basement membrane. The tubules were evaluated according to the following scoring system: 0= no tubular injury; 1#10% tubules injured; 2=11%-25% tubules injured; 3=26%-50% tubules injured; 4=51%-74% tubules injured; and 5$75% tubules injured.…”
Section: Quantitative Assessment Of Labeling Efficiencymentioning
confidence: 99%
“…Treatment of ischemic mice with the γ-secretase inhibitor DBZ ameliorated AKI and blocked Notch signaling with specific downregulation of Notch3, Dll4, Jag1 and the Notch target genes Hes1 , Hey2 , HeyL , Pdgfrb and Hif2a , suggesting that interventions targeting this cell-context-specific Notch signaling may be a feasible therapeutic approach. The reactivation of Notch signaling in acutely ischemic kidney and other tissues following ischemic injury has been observed in several studies Bielesz et al, 2010;Gupta et al, 2010;Huang et al, 2011;Liu et al, 2012;Chen et al, 2013;Sorensen-Zender et al, 2014]; however, whether this is beneficial for regeneration or has [Gupta et al, 2010] and blockade of Notch signaling with the γ-secretase inhibitor RO4929097 delayed functional and structural recovery , other studies, in line with this work, indicated the opposite effect, i.e. that the blockade of Notch signaling by the γ-secretase inhibitor DBZ or with a soluble Dll4 fusion protein promotes recovery from AKI or other acute ischemic tissue injuries [Huang et al, 2011;Liu et al, 2012;Sorensen-Zender et al, 2014] tors, Notch1-4, and 5 ligands, Dll1, Dll3, Dll4, Jag1 and Jag2.…”
Section: Discussionmentioning
confidence: 94%
“…For histologic examination, H&E staining was performed using the standard methods. 73 Immunohistochemistry and immunofluorescence staining were performed as described previously. 73,74 Briefly, rehydrated kidney sections were subjected to antigen retrieval using the Antigen Unmasking Solution purchased from Vector, followed by blocking with 2% normal goat serum.…”
Section: Administration Of Rapamycin To Tsc1 Ptko Mice and Examinatiomentioning
confidence: 99%
“…73 Immunohistochemistry and immunofluorescence staining were performed as described previously. 73,74 Briefly, rehydrated kidney sections were subjected to antigen retrieval using the Antigen Unmasking Solution purchased from Vector, followed by blocking with 2% normal goat serum. The sections were then incubated with primary antibodies (indicated in the respective figures) at 4°C overnight, washed three times in PBS, incubated with appropriate secondary antibodies, and washed with PBS again.…”
Section: Administration Of Rapamycin To Tsc1 Ptko Mice and Examinatiomentioning
confidence: 99%
See 1 more Smart Citation